178 A RETROSPECTIVE EVALUATION OF PROCESS OUTCOMES OF OLDER ADULTS REFERRED TO A COMMUNITY RE-ENABLEMENT TEAM FROM THE EMERGENCY DEPARTMENT. (18th November 2021) - Synnott, A; Ryan, C; O'Connell, P; Steed, F; Reale, S; Carey, L; English, S; Fitzgibbon, K; O'Connell, Á; Smalle, E; Ryan, D; Shchetkovsky, D; et al.
Abstract: Background: Emergency Departments (ED) are complex and challenging environments to provide care to older adults. There is currently a paucity of high quality methodological research investigating the effectiveness of interventions focused on transitions of care from the ED to primary care services (Hughes et al, 2019). This study aims to evaluate the impact of a collaborative model of care between primary and secondary care services for older adults discharged home following ED index visit. Methods: This was an observational retrospective study. Participants aged ≥65 years discharged home from the ED of a University Teaching Hospital and referred to a Multidisciplinary Community Intervention Team (MDCIT) were included. Referral pathways were via the OPTIMEND team (Cassarino et al, 2021) and MDCIT, which is a rapid access re-enablement team based in the community and compromises nursing staff, an occupational therapist, physiotherapist, therapy and healthcare assistants. Descriptive statistics were used to profile the baseline characteristics of study participants and to summarise data related to process outcomes. Ethical approval was granted for this study (020/2021). Results: In the study period, January—December 2020, 54 patients were referred to the MDCIT. The mean age of participants was 80.1 years (SD 8.2), 57% were female, and the most common Manchester Triage System presenting complaint was 'limb problems'. The median Patient Experience Time within the ED was 7.4 hours (IQR 13.1); 55% of participants were seen in their home within 24 hours of discharge. A mean of 10 interventions were delivered by the MDCIT. A 9.1% incidence rate of 30 day unscheduled hospital readmission was recorded. Conclusion: Integrated care programmes have been advocated to improve the continuum of care from the ED into the community. This evaluation has demonstrated the feasibility of implementing such a model of care. However, further methodologically robust research is required to advance the evidence base and should also focus on patient outcomes.